2008
DOI: 10.1021/ja076625f
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Biradical Character of Titanium Enolates

Abstract: Experimental and theoretical studies evidence an unconventional biradical character for the titanium enolates derived from α-alkoxy ketones and TiCl4. EPR experiments and ab initio calculations suggest that these titanium enolates have an open shell electronic ground state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 14 publications
2
37
0
Order By: Relevance
“…The stabilization of free radicals is necessary to avoid these problems. Fortunately, the introduction of a transition metal into the radical combination reactions provides an efficient approach to stabilize the radicals and protect them from being quenched by homo-coupling or fragmentation1011121314. Moreover, the interplay between a transition metal and radicals would be able to tune the reactivity of radicals and enable specific radical–radical cross-combination10151617.…”
mentioning
confidence: 99%
“…The stabilization of free radicals is necessary to avoid these problems. Fortunately, the introduction of a transition metal into the radical combination reactions provides an efficient approach to stabilize the radicals and protect them from being quenched by homo-coupling or fragmentation1011121314. Moreover, the interplay between a transition metal and radicals would be able to tune the reactivity of radicals and enable specific radical–radical cross-combination10151617.…”
mentioning
confidence: 99%
“…11 Although encouraging results were obtained with silyl ketene acetals (~50% yields, ds 3:1), the recent characterization of valence tautomerism in titanium enolates provided a conceptual foundation for the development of a direct radical chloroalkylation of N -acyl oxazolidinones. 12,13…”
mentioning
confidence: 99%
“…Moreira et al showed based on NMR, EPR, and computational studies that titanate enolates generated from TiCl 4 /a-alkoxy ketone complexes and tertiary amines display considerable biradical character. [12] These enolates must thus be considered unconventional valencetautomeric tetrachlorotitanate(IV) enolate/tetrachlorotitanate(III) a-carbonyl radical pairs 12/13 (Scheme 4).…”
mentioning
confidence: 99%